A case series of labial adhesion in reproductive age women - Dinku, Getu; Debas, Sintayehu; Yibeltal, Awoke; Siraw , Tadie (Ethiopian Journal of Reproductive Health, 2025)
Labial adhesion also known as labial fusion , labial agglutination or synechia vulvae . it is one of rare condition in reproductive age group unlike in prepubertal and postmenopausal women . We report two cases who were apparently health women presented with labial adhesion and surgical adhesiolysis was done in our hospital .